Ideas: Critical Realism of Moral-Material Complementarities - Rodney Shakespeare (University of Darussalam Gontor Press, 2023)
This section of JOCRISE is devoted to briefly ventilate innovative ideas on diverse perspectives of socio-scientiᢚc theories in general and developing economies particularly, for the common wellbeing of global holism. Writers may contribute ideas in this space for readers to gain theoretical, academic, and institutional insights